Combined Anterior and Posterior Decompression With Fusion for Cervical Ossification of the Posterior Longitudinal Ligament - Kuo, Chao-Hung; Kuo, Yi-Hsuan; Chang, Chih-Chang; Chang, Hsuan-Kan; Fay, Li-Yu; Wu, Jau-Ching; Huang, Wen-Cheng; Cheng, Henrich; Tu, Tsung-Hsi (Frontiers in Surgery, 2022)
Objective Cervical myelopathy caused by ossification of the posterior longitudinal ligament (OPLL) is not uncommon among Asian ethnic groups. Despite reports comparing the pros and cons of anterior- and posterior-only approaches, the optimal management remains debatable. This study aimed to evaluate the outcomes of patients who underwent a combined anterior and posterior approach, simultaneous circumferential decompression and fixation, for cervical OPLL. Method The study retrospectively reviewed patients with OPLL and who underwent circumferential decompression and fixation, combined anterior corpectomy and posterior laminectomy. The clinical outcomes were evaluated by the Visual Analogue Scale of neck and arm pain, the Japanese Orthopaedic Association scores, Neck Disability Index, and Nurick scores at each time-point of evaluation. Radiological evaluations included plain and dynamic radiographs and computed tomography for every patient within 2 years post-operation. Subgroup analyses were further performed between the groups, with and without intra-operative cerebrospinal fluid (CSF) leakage. Results A total of 41 patients completed the follow-up for more than 2 years (mean = 39.8 months) and were analyzed. Continuous-type OPLL was the most common (44%), followed by segmental (27%), mixed (22%), and localized types (7%) in the cohort. Myelopathy and all other functional outcomes improved significantly at 2 years post-operation (all p < 0.05). There were 13 (32%) patients who had intra-operative CSF leakage. At 2 years post-operation, there were no differences in the demographics, functional outcomes, and complication rates between the CSF-leakage and no-leakage groups. The CSF-leakage group had more patients with continuous-type OPLL than the no-leakage group (77% vs 29%, p = 0.004 < 0.05). During the follow-up, there was no secondary or revision surgery for pseudomenigocele, pseudarthrosis, or other surgery-related complications. Conclusions Simultaneous circumferential decompression and fixation combine the surgical benefits of sufficient decompression by the posterior approach and direct decompression of OPLL by the anterior approach. It is an effective surgical option for patients with cervical myelopathy caused by OPLL, given that myelopathy unanimously improved without neurological complications in this study. The fusion rates were high, and reoperation rates were low. Despite higher rates of CSF leakage, there were no related long-term sequalae, and minimal wound complications.